2021
DOI: 10.3390/foods10081779
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical, Structural, and Biological Properties of Crude Polysaccharides from Sweet Tea (Lithocarpus litseifolius (Hance) Chun) Based on Different Extraction Technologies

Abstract: Eight extraction technologies were used to extract sweet tea (Lithocarpus litseifolius (Hance) Chun) crude polysaccharides (STPs), and their chemical, structural, and biological properties were studied and compared. Results revealed that the compositions, structures, and biological properties of STPs varied dependent on different extraction technologies. Protein-bound polysaccharides and some hemicellulose could be extracted from sweet tea with diluted alkali solution. STPs extracted by deep-eutectic solvents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
(102 reference statements)
1
19
0
Order By: Relevance
“…The leaf of sweet tea has been approved as a new food material by the National Health and Family Planning Commission of China, which has also been utilized as an herbal tea to prevent and manage diabetes in the folk for a long history [ 1 , 2 ]. Generally, the leaf of sweet tea is rich in active ingredients, such as polysaccharides, flavonoids, phenolic acids, and triterpenoids [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, owing to these bioactive ingredients, it possesses multiple health benefits, such as antioxidant, anti-inflammatory, anti-diabetic, anti-cancer, anti-hypertensive, anti-microbial, cardioprotective, and hepatoprotective effects [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leaf of sweet tea has been approved as a new food material by the National Health and Family Planning Commission of China, which has also been utilized as an herbal tea to prevent and manage diabetes in the folk for a long history [ 1 , 2 ]. Generally, the leaf of sweet tea is rich in active ingredients, such as polysaccharides, flavonoids, phenolic acids, and triterpenoids [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ]. Therefore, owing to these bioactive ingredients, it possesses multiple health benefits, such as antioxidant, anti-inflammatory, anti-diabetic, anti-cancer, anti-hypertensive, anti-microbial, cardioprotective, and hepatoprotective effects [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that natural polysaccharides from edible and medicinal plants possess a variety of biological activities [ 9 , 10 , 11 , 12 ], which have attracted increasing attention in the functional food industry. However, the knowledge about the chemical structures and biological functions of sweet tea polysaccharides is still limited [ 5 ], which requires to be deeply investigated so as to promote its applications in the functional food industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithocarpus litseifolius [Hance] Chun, also popularly called "sweet tea", is a herbal plant with an evident sweet taste that has been accepted as a daily beverage in the south of China for more than 1000 years, and was approved as a new food material in China in 2017 [1,2]. The major bioactive components in sweet tea include flavonoids and polysaccharides; dihydrochalcones are the main flavonoids [3,4]. Until now, many health benefits have been reported of sweet tea, such as antioxidant, antihypertensive, antihyperlipidemic, antihyperglycemic, anti-inflammatory, antimicrobial, and anticancer effects [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Lithocarpus litseifolius (Hance) Chun, which has abundant wild resources in the mountainous region of southern China, is commonly named as “sweet tea” [ 36 ]. Sweet tea has been listed as a new food resource by the National Health and Family Planning Commission of China since 2017 [ 9 ]. Its leaves, which function as tea, sugar and medicine, have been used as a traditional herbal medicine and tea, and it has the potential to become a functional food and food additive [ 26 ].…”
Section: Introductionmentioning
confidence: 99%